Multilingualism and code-switching in subtitle translation: a case study of the Malaysian film Guang - Tong, Miao Ying (Nanyang Technological University, 2022)
Malaysia has always been known for its multiculturalism and multiethnicity, and Malaysians are known for their multilingualism. In Malaysian films, code-switching and the appearance of multilingualism is prevalent, and it goes against the standard language ideology. While various elements such as culture and history are thought to influence the formation of language, this study article seek to assess how to preserve the authenticity of Malaysian Chinese films, as well as if they are worth preserving and promoting. If so, what would be the better approach to the translation of this type of text? A case study on the Malaysian film Guang was chosen for the investigation due to the reality it reflects. The verbatim of the dialogues was extracted and recorded in a table from the film, together with the Chinese subtitles, to quantify the occurrence of different languages. Further analysis was carried out to understand the reasoning of the speaker, and lastly, translation procedures were suggested in order to improve the quality of audiovisual translation output, with a focus on code-switching and multilingualism. This research also serves as a useful reference for Malaysian translators.